GATHER THE SCATTERED IN KAILI LAND: Pluralism, Religiosity, and Integration of Central Sulawesi Society - Andriansyah Andriansyah; Syakir Mahid; Ismail Suardi Wekke (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2018)
Abstract: Based on the ethnic division of the population, Central Sulawesi Province consists of 12 ethnics groups “original,” and many tribal immigrants such as Bugis, Makassar, Java, Bali, and other tribes that have implications for the differentiation of indigenous communities and immigrant communities. The diversity of the tribes is also accompanied by the diversity of their historical background, religion, and culture which might cause friction one another. Based on the existing historical reality, it is showed that the Central Sulawesi region is often hit by ethnic, economic, and religious violences with different intensity. If the diversity among the people of Central Sulawesi is not properly managed, it can lead to disintegration. This article would identify the existence of the plural society in Central Sulawesi and try to formulate the integration efforts of the people of Central Sulawesi.Abstrak: Mengumpul yang Berserak: Pluralisme, Religiositas, dan Integrasi Masyarakat Sulawesi Tengah. Berdasarkan pembagian etnis penduduk, Provinsi Sulawesi Tengah terdiri atas dari 12 etnis asli, dan banyak juga suku pendatang seperti Suku Bugis, Makassar, Jawa, dan Bali yang berimplikasi pada diferensiasi masyarakat asli dan masyarakat pendatang yang berpotensi menimbulkan gesekan antara satu dengan lainnya. Realitas historis menunjukkan bahwa wilayah Sulawesi Tengah sering dilanda kekerasan bermotif etnis, ekonomi dan agama dengan intensitas yang berbeda-beda. Keanekaragaman pada masyarakat Sulawesi Tengah, apabila tidak ditata dengan baik dapat mengakibatkan disintegrasi. Tulisan bertujuan menganalisis keberadaan masyarakat plural Sulawesi Tengah dan mencoba merumuskan upaya integrasi masyarakatnya.Keywords: pluralism, religiosity, Central Sulawesi, integration